Meta-Analysis of Music Therapy Efficacy as Intervention for Sleep Disorders - Sasmita, Jonathan; Yudiarso, Ananta (Kuras Institute, 2025)
Sleep is a fundamental biological process critical for cognitive function, emotional regulation, and physical health. Despite its importance, sleep disorders have become increasingly prevalent globally, contributing to reduced quality of life, impaired daily functioning, and elevated risks for chronic illnesses, for example cardiovascular disease and depression. Current treatments, such as pharmacotherapy and cognitive-behavioral therapy, also have limitations such as limited accessibility, side effects, and costs, therefore there is a need for alternative, low-risk, and accessible intervention to improve sleep quality. Music therapy, as a non-invasive and cost-effective approach, appears as a promising candidate, but requires systematic evaluation to establish its efficacy. This meta-analysis investigates the effectiveness of music therapy for individuals experiencing sleep disorders. A systematic review of prior studies was conducted; Egger’s regression test confirmed the absence of publication bias (p >0.05). Results demonstrated a large effect size (Hedge’s g =1.29), indicating that music therapy substantially enhances sleep quality. Future research should incorporate objective sleep measurements such as electroencephalography (EEG) and actigraphy, alongside subjective self-reports. Utilizing objective sleep monitoring technologies should further our knowledge regarding the mechanisms underlying music’s effects on sleep. Overall, this study reinforces viability of music therapy as an accessible and effective tool for managing sleep disorders and emphasizes the need for continued rigorous research.